Pengaruh Postur Motivasi Terhadap Kepatuhan Wajib Pa-jak Bumi Dan Bangunan (PBB) - Ameldan Alchair, Achmad Rifadi; Prihatiningtias, Yeney Widya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to examine the effect of motivational posture on land and building taxpayer compliance (PBB) in Malang City during the Covid-19 pandemic through 5 variables, namely commitment, capitulation, resistance, release, and playing games. The object of this research is 100 residents of Malang City who have become Land and Building Taxpayers. Data analysis was performed using multiple linear regression methods with the SPSS application. Based on the results of the research that has been carried out, it can be seen that the commitment variable has a positive effect on land and building taxpayer (PBB) compliance in Malang City, while the capitulation variable has no positive effect on land and building taxpayer (PBB) compliance in Malang city. Then, on the variable resistance, disengagement and game playing have a negative effect on the compliance of the Land and Building Taxpayer (PBB) in Malang City. This shows that paying land and building taxes is the right thing and people are responsible for their obligations by paying taxes according to actual calculations and conditions. This shows that taxpayers have the motivation to commit to carrying out tax obligations and comply with applicable tax regulations.